Sacred ritual, profane space: the Roman house as early Christian meeting place - Cianca, Jenn (Studies in Christianity and Judaism, 2018)
"This monograph examines the nature of the earliest Christian meeting places, with a special emphasis on the formation of sacred space. The use of domestic spaces by these early groups is widely accepted, but the spaces themselves are usually understood as having been neutral, rather than sacred. In this study, I propose not only that these domestic spaces were considered sacred space by the Christian communities that used them, but that they were also complex ritual loci in their own right. Mapping what is known from early Christian texts onto the archaeological data for Roman domestic space here provides a new lens through which to examine the relationship between early Christians and their meeting space. In many cases, this meeting space would have included the presence of the Roman domestic cult. Despite the fact that the domestic cult was a polytheistic one, at odds with monotheistic Christianity, I assert that its practices likely continued in those places used for worship by the Christians. I also argue that continued practice of the domestic cult in Roman domestic spaces did not preclude the house-church Christians from understanding their rituals or their meeting places as sacred. Theories of sacred space and ritual practice are engaged to demonstrate that the house-church Christians constructed temporary sacred space through ritual enactment. The exploration of meeting places as both inhabited and sacred space raises a host of questions about early Christian identity, ritual affiliation, and domestic practice."--